Pregnancy outcome in patient with rare autoimmune disease with complex cardiac ailment - Anuragi, Hansika; Gaikwad, Harsha S.; Pandey, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Takayasu arteritis (TA), a rare chronic granulomatous vasculitis of the aorta and its major branches, poses significant challenges in pregnancy, including an increased risk of hypertension, pre-eclampsia, intrauterine growth restriction (IUGR), and maternal cardiac decompensation. We present the case of a 22-year-old, G2A1 woman at 38 weeks and 3 days of gestation, with a known history of TA and a blockade of the left main coronary artery requiring stent placement. Her pregnancy was managed by a multidisciplinary team. Antihypertensive therapy (Metoprolol and Torsemide) was carefully titrated, and Ecospirin was discontinued prior to delivery. An elective lower segment caesarean section (LSCS) under invasive haemodynamic monitoring was performed at 38 weeks, resulting in the delivery of a healthy infant and favourable maternal outcome. This case underscores that with meticulous, multidisciplinary antenatal care, strategic medication management, and timed delivery, successful pregnancy outcomes are achievable in women with TA, even with a history of severe coronary involvement. It aligns with literature advocating for individualised care plans in this high-risk obstetric population.